Condensed versus standard schedule of high-dose cytarabine consolidation therapy with pegfilgrastim growth factor support in acute myeloid leukemia - Jaramillo Segura, Sonia; Benner, Axel; Schlenk, Richard Friedrich (Blood cancer journal, 2017)
The aim of this cohort study was to compare a condensed schedule of consolidation therapy with high-dose cytarabine on days 1, 2 and 3 (HDAC-123) with the HDAC schedule given on days 1, 3 and 5 (HDAC-135) as well as to evaluate the prophylactic use of pegfilgrastim after chemotherapy in younger patients with acute myeloid leukemia in first complete remission. One hundred and seventy-six patients were treated with HDAC-135 and 392 patients with HDAC-123 with prophylactic pegfilgrastim at days 10 and 8, respectively, in the AMLSG 07-04 and the German AML Intergroup protocol. Time from start to chemotherapy until hematologic recovery with white blood cells >1.0 G/l and neutrophils >0.5 G/l was in median 4 days shorter in patients receiving HDAC-123 compared with HDAC-135 (P<0.0001, each), and further reduced by 2 days (P<0.0001) by pegfilgrastim. Rates of infections were reduced by HDAC-123 (P<0.0001) and pegfilgrastim (P=0.002). Days in hospital and platelet transfusions were significantly reduced by HDAC-123 compared with HDAC-135. Survival was neither affected by HDAC-123 versus HDAC-135 nor by pegfilgrastim. In conclusion, consolidation therapy with HDAC-123 leads to faster hematologic recovery and less infections, platelet transfusions as well as days in hospital without affecting survival.
Published online 26 May 2017
Gesehen am 14.08.2018